2015
DOI: 10.1016/j.ress.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the treatment of uncertainty in Bayesian networks and fuzzy expert systems used for a human reliability analysis application

Abstract: The use of expert systems can be helpful to improve the transparency and repeatability of assessments in areas of risk analysis with limited data available. In this field, Human Reliability Analysis (HRA) is no exception, and, in particular, dependence analysis is an HRA task strongly based on analyst judgement. The analysis of dependence among Human Failure Events refers to the assessment of the effect of an earlier human failure on the probability of the subsequent ones. This paper analyses and compares two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Since human reliability analysis is still at the starting stage in power systems, and related data statistics is still very scarce. The use of expert systems, such as fuzzy expert systems, can be helpful to improve the assessments with limited data available [27]. In this paper, triangular fuzzy model is used to lower subjectivity of judgment [28].…”
Section: Process-centered Hra (Pchra)mentioning
confidence: 99%
“…Since human reliability analysis is still at the starting stage in power systems, and related data statistics is still very scarce. The use of expert systems, such as fuzzy expert systems, can be helpful to improve the assessments with limited data available [27]. In this paper, triangular fuzzy model is used to lower subjectivity of judgment [28].…”
Section: Process-centered Hra (Pchra)mentioning
confidence: 99%
“…Risk priority number (RPN) is another common method to evaluate the product failure effect from the experts' perspective of severity, occurrence, and detectability [17,18]. Fuzzy theory decreases the subjective preference of decision makers and has been used in expert evaluation like fuzzy AHP [19] and fuzzy expert systems [20]. On the contrary, Wang et al [21] and Yang et al [17] demonstrated that collecting field data are time-consuming, and they took several years to collect the number of field data from NC machine tools.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as an advanced technology of uncertainty knowledge representation and inference, the Bayesian network (BN) is widely applied to the reliability analysis [4], risk analysis [5], fault diagnosis [6] of the complex system, etc.…”
Section: Introductionmentioning
confidence: 99%